"That . . . the Father of glory, may give you a spirit of wisdom": Δωη in Ephesians 1.17 and 2 Timothy 2.25. Issue 2 (August 2020) - Harmai, Gábor
The spelling of δώῃ in NA28 in Eph 1.17 and 2 Tim 2.25 is wrong. The correct form is δῴη, as in Westcott and Hort (WH), and a number of other old editions. An additional difficulty is that the NA apparatus does not illuminate the problem for the reader as the WH editions do. The problem is not serious in the translation of 2 Tim 2.25, where the real problem is the translation of μήποτε. In any case, if the verb is an optative, expressing a wish, we can understand better the irony of the author. Translations of Eph 1.17 that read δωη as subjunctive (expressing possibility) rather than optative are erroneous: The verb is in fact optative, as earlier translations correctly reflect.